2019
DOI: 10.1155/2019/6936049
|View full text |Cite
|
Sign up to set email alerts
|

Digital Workflow for Indirect Bonding with 2D Lingual Brackets: A Case Report and Procedure Description

Abstract: Objective. During orthodontic therapy, accuracy in bonding procedures makes it easier to correct tooth alignment by decreasing the need for midcourse corrections by changing bracket positions. Indirect bonding allows the transfer of the appliance components from model casts to patient’s teeth potentially meaning shorter appointments for bracket bonding and rebonding and best comfort during chairside practice. At the same time, there has been a steady increase in requests for invisible lingual orthodontic treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…However, most of these studies are conducted in adult patients, while a large percentage of the volume of orthodontic patients are children and/or adolescents. After the results obtained in the search in the databases, it is relevant that many of the studies had to be excluded from the analysis because they were in vitro studies ( 11 , 21 24 ) or with adult subjects or not reported age of the patients ( 4 , 5 , 25 27 ). Some of the studies have resulted in low population extrapolation because they have studied children in the adolescent stage, ignoring younger children who are precisely the ones that present the most behavioral problems during impressions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of these studies are conducted in adult patients, while a large percentage of the volume of orthodontic patients are children and/or adolescents. After the results obtained in the search in the databases, it is relevant that many of the studies had to be excluded from the analysis because they were in vitro studies ( 11 , 21 24 ) or with adult subjects or not reported age of the patients ( 4 , 5 , 25 27 ). Some of the studies have resulted in low population extrapolation because they have studied children in the adolescent stage, ignoring younger children who are precisely the ones that present the most behavioral problems during impressions.…”
Section: Discussionmentioning
confidence: 99%
“…Among the benefits of intraoral scanning systems are real-time visualization, ease and selectivity of repetition, selective capture of areas of interest, shorter disinfection time than conventional impressions, image analysis options, absence of model wear, ease of archiving and data fusion, among others ( 1 , 3 ). In addition, patients report that the perception and comfort of the intraoral scanner is better than with conventional impressions ( 4 , 5 ). However, the intraoral scanners have some limitations such as the existence of a higher learning curve, the inability to modify the occlusion of the patient, the high costs of the system and the rigid sequence of scanning ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, digital impressions combined with CAD/CAM technology allow a completely digital workflow, starting from impression to framework planning, to realization of final work. This completely digital workflow has been demonstrated to be effective in various fields of dentistry, such as prosthodontics, conservative dentistry, and orthodontics . The digital models, however, obtained through intraoral scans are not fully integrated into private practices that are as durable as conventional methods .…”
Section: Introductionmentioning
confidence: 99%
“…Generalmente se utiliza en brackets linguales personalizados 3D, aunque en el reporte de un caso se usó brackets linguales estándar 2D (16). Fue una opción de bajo costo para casos leves y de dobleces de primer y segundo orden repetible y eficaz.…”
Section: Cementación Indirectaunclassified